2016
DOI: 10.1515/ijame-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Industrial noise level study in a wheat processing factory in ilorin, nigeria

Abstract: An industrial process such as wheat processing generates significant noise which can cause adverse effects on workers and the general public. This study assessed the noise level at a wheat processing mill in Ilorin, Nigeria. A portable digital sound level meter HD600 manufactured by Extech Inc., USA was used to determine the noise level around various machines, sections and offices in the factory at pre-determined distances. Subjective assessment was also mode using a World Health Organization (WHO) standard q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…These results are in accordance with the results obtained from the study. Highest noise levels in a wheat processing factory in Nigeria was 99.4 dB(A) (Ibrahim et al, 2016) which was in agreement with the results obtained in the study where two machines were operating at a distance of 50 cm. Boateng and Amedofu (2004) reported noise levels in corn mills to exceed the limiting value of 85 dB(A) as recommended by NESREA.…”
Section: Number Of Flour Millssupporting
confidence: 89%
“…These results are in accordance with the results obtained from the study. Highest noise levels in a wheat processing factory in Nigeria was 99.4 dB(A) (Ibrahim et al, 2016) which was in agreement with the results obtained in the study where two machines were operating at a distance of 50 cm. Boateng and Amedofu (2004) reported noise levels in corn mills to exceed the limiting value of 85 dB(A) as recommended by NESREA.…”
Section: Number Of Flour Millssupporting
confidence: 89%
“…In recent decades, noise pollution has emerged as one of the most significant environmental problems due to rapid urbanization and fast expansion of industrial operations. [1][2][3] Industrial noise is one of the most annoying and tiring factors in working environments, be it in factory, workshop, academic or research setup. [4][5][6][7][8][9] Studies have revealed that noise of factories/workshops account for about 80% noise pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The result of the study revealed the average noise level produced by the machines to be 99.4 dBA which was beyond human standard of hearing. It was further recommended that room acoustics should be upgraded for workers to absorb sound transmitted to offices" [9]. Christopher et al [5] assessed traffic noise pollution and a survey on residents' health at Alimosho local government Lagos, Nigeria.…”
Section: Introducutionmentioning
confidence: 99%